Study on probable aetiological factors of subfertility in a tertiary care hospital - Lamsal, Manoj; Tamrakar, Suman Raj (Journal of Kathmandu Medical College, 2022)
Background: Subfertility refers to describe women or couple who are not sterile but exhibit decreased reproductive efficiency even after 12 months of regular unprotected intercourse. Objectives: To find probable aetiological factors in subfertile couples attending Dhulikhel Hospital. Methods: This descriptive cross-sectional study was conducted among 140 subfertile couples in Dhulikhel Hospital from March 2016 to December 2017 after ethical clearance. The participants were recruited by convenience sampling, data were entered in Microsoft Excel Sheet and analysed using SPSS v.23. Descriptive statistics like frequency, percent, mean, and standard deviation have been presented. Results: Among 140 subfertile couples, mean duration of subfertility was 5.55 ± 3.96 years. About two-thirds (95, 67.9%) of them were of primary subfertility. Most subfertile clients (both) were of 26-30 years age group and about three-fifths (83, 59.3%) were of Janajati caste. The most common cause of subfertility was female factor (72, 51.4%) only. Ovulatory dysfunction (49, 35%) followed by tubal abnormalities (24, 17.1%) were major female contributory factors. Thyroid disorder was noted in 19 (13.6%) clients and hyperprolactinaemia was observed in 14 (10%) subfertile female clients. Two (1.4%) female clients had diabetes mellitus and 24 (17.1%) had evidence of different forms of genital infection. Only male factor contributed was seen in 16 (11.4%) clients and asthenozoopermia was the commonest abnormal semen parameters. Six (4.3%) males with abnormal semen parameter were working abroad. Conclusion: Ovulatory causes was found to be the commonest cause of subfertility in Dhulikhel Hospital. Asthenooospermia was the most common male factor.